The mediating role of holistic thinking in enhancing High-Order Thinking Skills (HOTS) teaching practices - Embong, Rahimah; Hashim, Huda Afiqah; Bahardin, Zainal; Wan Yusoff, Wan Mazwati; Mohd Yusoff, Zurita (Iated Digital Library, 2024)
In the evolving educational landscape of the 21st century, mastery of higher-order thinking skills (HOTS) is critical for students to meet globalisation's challenges effectively. Despite targeted initiatives by the Ministry of Education in the country of Malaysia, as delineated in the Malaysian Education Blueprint 2013-2025, assessments like the Trends in International Mathematics and Science Study (TIMSS) and Programme for International Student Assessment (PISA) reflect suboptimal HOTS outcomes among students. This suggests potential gaps in the effectiveness of current teaching practices. This paper examines the interplay between teachers’ knowledge of HOTS, their teaching practices, and holistic thinking behaviour. It investigates whether holistic thinking is a mediating factor in enhancing teaching efficacy in Malaysian secondary schools. Employing a quantitative approach, this study surveyed 220 teachers from six national secondary schools specializing in religious education in Terengganu. The survey instruments, informed by the Theory of Holistic Thinking Behavior and Socratic Questioning, were validated by three domain experts. Data analysis was conducted using Structural Equation Modeling (SEM) to evaluate mediation effects and the direct impacts of teacher knowledge and holistic thinking on HOTS teaching practices. The study identified robust levels of HOTS knowledge, effective teaching practices among teachers, and a significant presence of holistic thinking behaviours, including metacognition, creative, and flexible thinking. SEM results demonstrated that holistic thinking behaviour significantly mediates the relationship between HOTS knowledge and teaching practices. The findings underscore the need for professional development programs that enhance teachers’ holistic thinking skills to improve HOTS teaching effectiveness. The study proposes a Model of Effective HOTS Teaching, suggesting that strengthening teachers' holistic thinking can lead to more effective implementation of HOTS pedagogy. By reinf orcing the role of holistic thinking in educational settings, this research contributes to the theoretical and practical enhancement of teaching strategies, potentially influencing educational policies and practices on a global scale. The Model of Effectiv e HOTS Teaching offers a framework for educators worldwide to refine their approach to teaching higher-order thinking skills, aligning with global educational standards and expectations.